LITERACY EVENT SEBAGAI KAMPANYE PUBLIC RELATIONS DALAM MENINGKATKAN SEMANGAT LITERASI MASYARAKAT INDONESIA - Anisa Diniati; Razie Razak; Martha Tri Lestari (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
Tel-U Literacy Event 2021 seeks to embrace various pentahelix elements to call for the spirit of literacy so that they can provide knowledge that can be utilized in improving people's welfare. This study aims to explore what Public Relations campaign strategies are being carried out to increase the literacy spirit of the Indonesian people. The type of research used is descriptive research using a qualitative approach. The primary data sources used are the results of observations and interviews with key informants, supporting informants, and expert informants in the field of event management, public relations campaign management, and literacy. The results showed that in implementing the Public Relations campaign strategy in increasing the spirit of literacy, there are five main stages consisting of situation analysis, planning programming, pentahelix strategy, Taking Action Communication, and monitoring evaluation. Situation analysis and monitoring evaluation are two interconnected stages, this stage the Literacy Event routinely conducts After Action Review activities in order to find out the advantages and disadvantages of the events being held. Through these three activities, Literacy Event is much easier to determine the purpose of the activity, target audience, themes and topics, until the implementation of the activity takes place.